2015
DOI: 10.1007/s00284-015-0858-y
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Composition and Biofilm Production of Attenuated Salmonella typhimurium dam and seqA Mutants After Exposure to UV-C

Abstract: The goal of this work was the investigation of correlation between some peculiarities of membrane fatty acids composition, biofilm formation, and motility of dam and/or seqA mutants in Salmonella typhimurium bacterial cells and UV-C radiations. The exposure changed the fatty acids composition of dam and seqA/dam strains. Significant increase of unsaturated fatty acids was observed. Swarming and swimming were enhanced only in dam mutant and biofilm formation increased significantly in all tested strains after U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In both dam and seqA mutants, the Dam methylase and SeqA proteins encoded by the respective genes probably perform these activities by altering the activity of the RNA polymerase or transcription factors in the promoter regions. It was previously determined that SeqA and Dam proteins might regulate fatty acid biosynthesis of Salmonella Typhimurium and membrane fluidity might cause changes in flagella and exopolysaccharide which are involved in the biofilm formation [23]. In our work, the changes observed in the biofilm formation of dam and seqA mutants may also lead to changes in the composition of the cell membranes due to these mutations.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…In both dam and seqA mutants, the Dam methylase and SeqA proteins encoded by the respective genes probably perform these activities by altering the activity of the RNA polymerase or transcription factors in the promoter regions. It was previously determined that SeqA and Dam proteins might regulate fatty acid biosynthesis of Salmonella Typhimurium and membrane fluidity might cause changes in flagella and exopolysaccharide which are involved in the biofilm formation [23]. In our work, the changes observed in the biofilm formation of dam and seqA mutants may also lead to changes in the composition of the cell membranes due to these mutations.…”
Section: Discussionmentioning
confidence: 63%
“…It was shown in certain bacteria, such as Salmonella typhimurium, Escherichia coli and Acinetobacter baumannii, that biofilm formation is under epigenetic regulation [14,19,45]. However, there are a few articles describing the effect of dam methylation on biofilm formation in Salmonella [19,23]. Aya Castaneda et al [19] have found that DNA methylation in S. enteritidis upregulates the expression of biofilm production factors such as cellulose and curli by modifying the csgD expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations